Full‐State Synthesis of Electromagnetic Fields using High Efficiency Phase‐Only Metasurfaces. (23rd July 2020) - Wu, Jun Wei; Wang, Zheng Xing; Fang, Zu Qi; Liang, Jing Cheng; Fu, Xiaojian; Liu, Jun Feng; Wu, Hao Tian; Bao, Di; Miao, Long; Zhou, Xiao Yang; Cheng, Qiang; Cui, Tie Jun
Abstract: A metasurface is a thin array of subwavelength elements with designable scattering responses, and metasurface holography is a powerful tool for imaging and field control. The existing metasurface holograms are classified into two types: one is based on phase‐only metasurfaces (including the recently presented vectorial metasurface holography), which has high power efficiency but cannot control the phases of generated fields; while the other is based on phase‐amplitude‐modulated metasurfaces, which can control both field amplitudes and phases in the region of interest (ROI) but has very low efficiency. Here, for the first time, it is proposed to synthesize the field amplitudes and phases in ROI simultaneously and independently by using high‐efficiency phase‐only metasurfaces. All points in ROI may have independent values of field amplitudes and phases, and the requirements for X and Y components may be different in achieving spatially varied polarization states. To this end, an efficient design method based on equivalent electromagnetic model and gradient‐based nonlinear optimization is proposed. Full‐wave simulations and experimental results demonstrate that the phase‐only metasurface designed by the method has 10 times higher efficiency than the phase‐amplitude‐modulated metasurface. This work opens a way to realize more complicated and high‐efficiency metasurface holography. Abstract : For the first time, a high efficiency phase‐only metasurface is used to synthesize field amplitudes and phases simultaneously and independently. Different requirements can be impressed on orthogonal field components, thus achieving spatially varied polarizations. To this end, an efficient method utilizing equivalent electromagnetic model and gradient‐based optimization is proposed. The presented design has 10 times higher efficiency than phase‐and‐amplitude metasurfaces.